Dampak Sosial dan Ekonomi Minimnya Angkutan Umum Terhadap Masyarakat Kota Palangka Raya - Wawan M. Marbun; Melati Sinaga; Yuni C Sembiring; Try Santi Situmorang; Ucok Ucok; Suherman Suherman (Pusat Riset dan Inovasi Nasional, 2024)
This research examines the social and economic impacts of the lack of public transport on the people of Palangkaraya City. The lack of public transport in the city has become a major impediment to mobility, resulting in higher living costs and longer travel times. Using qualitative methods, this study evaluates how the lack of public transport affects the daily lives of residents, including access to employment, and education.The results show that the lack of public transit has led to increased use of private vehicles, which contributes to traffic congestion and air pollution. In addition, low-income residents who cannot afford private vehicles or pay expensive transportation fares become isolated and experience greater economic hardship. Based on this research we recommend improving public transport infrastructure, developing more efficient routes and schedules, and subsidizing fares for low-income groups. In addition, cooperation between the government, private sector, and civil society is needed to create sustainable and inclusive transportation solutions. mproving the public transport system is expected to improve the quality of life of Palangkaraya citizens and support more balanced economic growth.